RUSSIA'S VETO IN REJECTING THE DRAFT OF UN SECURITY COUNCIL RESOLUTION ON SYRIA - Mahreta Adi Kuncoro (2013)
The crisis in Syria is essentially a result of the upheaval of the Middle East countries revolution. The case was no any longer of Syria's domestic affair but it had become international affairs since there are number of casualties from the opposition party. The international community strictly condemned the Syrian government for its military approach. The international responses were proven by the submission of the draft of the UN Security Council resolution on Syria, led by the West and its al